Water phase condition in the butter paste with red beet powder - Podkovko, Oksana; Rashevska, Tamara (My University, 2015)
The technology of butter paste with red beet powder based on butter with addition of dry skimmed milk, flaxseeds and inulin is developed. The quantity of the plant food additives in the ready product is red beet powder - 0.80 %, inulin — 1.50 %, flaxseeds - 2.90 %. The condition of the water phase in the fresh product was investigated for the indicators: dispersion of plasma and forms of moisture connection. Dispersion was determined by computing the drops of moisture under the microscope MICROmed XS-2610. The article concludes that the adding of red beet criopowder. flaxseeds, inulin with simultaneously mechanical processing provokes dispersion of moisture in the butter paste with increasing droplets with the diameter of 1...5 microns. Main forms of moisture connection research were conducted by thermogravimetry method with derivatograph Pauli-Erdene 0-1500 D system. These results suggest that the selected complex of plant food additives leads to increasing amount of monomolecular and polymolecular firmly bound moisture.
Keywords: butter paste; масляна паста; масляная паста; кафедра технології молока і молочних продуктів